1985
DOI: 10.1002/jlac.198519851105
|View full text |Cite
|
Sign up to set email alerts
|

Untersuchungen zur Darstellung von Desoxyzucker‐Steroidglycosiden

Abstract: In stereoselektiven Reaktionen lassen sich die Glycale 1, 2 und 8 mit Cholesterin sowie Digitoxigenin nach dem N-Iodsuccinimid-Verfahren zu den 2-Desoxy-2-iod-a-glycosiden 3, 4 , s und 9 kondensieren. Bei den langsamen Umsetzungen treten die direkten N-Iodsuccinimidaddukte wie z.B. 6 als Nebenprodukte auf. In Butanon reagiert 11 nur teilweise zu den erwarteten Glycosiden 12 bzw. 13, bevorzugt bilden sich die Hex-2-enopyranoside 17 bzw. Studies on the Synthesis of Stereoid Glycosides of Deoxy Sugars')The 2-deo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…For example, silver silicate was developed by Paulsen and co-workers for β-selective couplings. 55 , 56 While Thiem and co-workers found that this catalyst was not effective in their studies on the synthesis of digitoxin, 57 Binkley and co-workers found that it was useful for the construction of β-linked olivose sugars commonly found in the anthracycline antitumor antibiotics. 58 , 59 Interestingly, selectivity in these couplings appeared to be dependent on the acceptor.…”
Section: Direct Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…For example, silver silicate was developed by Paulsen and co-workers for β-selective couplings. 55 , 56 While Thiem and co-workers found that this catalyst was not effective in their studies on the synthesis of digitoxin, 57 Binkley and co-workers found that it was useful for the construction of β-linked olivose sugars commonly found in the anthracycline antitumor antibiotics. 58 , 59 Interestingly, selectivity in these couplings appeared to be dependent on the acceptor.…”
Section: Direct Synthesismentioning
confidence: 99%
“…Heterogeneous silver catalysts can offer advantages in these reactions in terms of both product purification and selectivity of the glycosylation reaction. For example, silver silicate was developed by Paulsen and co-workers for β-selective couplings. , While Thiem and co-workers found that this catalyst was not effective in their studies on the synthesis of digitoxin, Binkley and co-workers found that it was useful for the construction of β-linked olivose sugars commonly found in the anthracycline antitumor antibiotics. , Interestingly, selectivity in these couplings appeared to be dependent on the acceptor. With a 4-tosyl-protected acceptor 25a , the glycosylation with an olivose bromide donor 24 produced disaccharide 26a in 84% yield with good selectivity (1:11 α:β).…”
Section: Direct Synthesismentioning
confidence: 99%
“…This leads to glycosyl succinimides which can adopt predominantly an inverted ' C d (D) chair conformation [30]. To this respect, nucleophilicity of the alcohol can be increased by a previous 0-tributylstannylation which allows better reactivity in NIS-promoted addition to glycals (excellent results are thus obtained with the axially configurated 4-hydroxy group of various L-fucose derivatives) [ 3 11.…”
Section: Bromo-and Iodoalkoxylation Of Glycalsmentioning
confidence: 99%
“…3 The same promoters were successfully used for the synthesis of steroid 2-deoxy-a-glycosides and oligosaccharides. 4,5 In a continuation of our studies we extended a number of biologically active triterpenes and steroid alcohols used and carried out giycosylation of methyl esters of 18a-(la), II-deoxo-(lb), and 18,19-dehydroglycyrrhetic acids (le) with di-O-acetyl-u-rhamnal (2) and acetylcholic acid methyl ester (ld) with tri-O-acetyI-t~-glucal (3) in the presence of IDCP.…”
mentioning
confidence: 99%